1994
DOI: 10.1111/j.1365-2109.1994.tb00735.x
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of triploid induction by the use of 6-DMAP for the oyster Crassostrea gigas (Thunberg)

Abstract: Abstracl. A nove! mcthod using 6-dimcthylaminopurinc (6-0MAP) has rcccntly bccn dcmonstrated to bc a good triploid inductor for bivalvc molluscs. Thc cffccts of 6-0MAP concentration, timing of trcatment aftcr fertilization. and treatment duration on survival and triploid induclion of Crassastrea gigas (Thunberg) embryos wcre examined. A.n influcnce of sperm concentration was also detected and discussed. Survival loO-stage was invcrscly re!ated to 6-0MAP concentration and the percentage of triploids was shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 7 publications
4
15
0
1
Order By: Relevance
“…This suggests that results can be improved by optimizing the induction protocols (Surier et al, 2007;Toro et al, 1995). (Desroisers et al, 1993;G erard, Naciri, Peignon, Ledu, & Phelipot, 1994). The percentage of triploid larvae obtained in the present study is similar to that reported in Crassostrea gigas (22%-57%) using this 6-DMAP at higher concentrations (390-450 lM/L) and a similar exposure time (Melo, Gomes, Silva, S€ uhnel, & Melo, 2015).…”
Section: Post-larvae Survival and Growthsupporting
confidence: 86%
See 1 more Smart Citation
“…This suggests that results can be improved by optimizing the induction protocols (Surier et al, 2007;Toro et al, 1995). (Desroisers et al, 1993;G erard, Naciri, Peignon, Ledu, & Phelipot, 1994). The percentage of triploid larvae obtained in the present study is similar to that reported in Crassostrea gigas (22%-57%) using this 6-DMAP at higher concentrations (390-450 lM/L) and a similar exposure time (Melo, Gomes, Silva, S€ uhnel, & Melo, 2015).…”
Section: Post-larvae Survival and Growthsupporting
confidence: 86%
“…The treatment with 6‐DMAP (300 μM/L for 15 min) resulted in the best induction efficiency/effectiveness with a 39% of A. nucleus triploid larvae. This chemical inhibits the phosphorylation of proteins required in the process of tubulin microtubules polymerization and formation of the spindle apparatus through which segregation of the chromosomes during cellular division occurs (Dufresne, Néant, Saint‐Pierre, Dubé, & Guerrier, ; Rimme, Neant, Guerrier, & Ozon, ; Szöllösi et al., ), thus inhibiting the formation of polar bodies (Desroisers et al., ; Gérard, Naciri, Peignon, Ledu, & Phelipot, ). The percentage of triploid larvae obtained in the present study is similar to that reported in Crassostrea gigas (22%–57%) using this 6‐DMAP at higher concentrations (390–450 μM/L) and a similar exposure time (Melo, Gomes, Silva, Sühnel, & Melo, ).…”
Section: Discussionmentioning
confidence: 99%
“…Using stripped gametes is more expedient and practical for producing tetraploids than using spawned oocytes because the time of fertilization and duration of treatment can be easily controlled (Jose & Meredith, ). Synchronization of meiosis of eggs is critical for the induction ratio of tetraploid and triploid oysters (Downing & Allen., ; Gerard, Naciri, Peignon, Ledu, & Phelipot, ). For example, Downing and Allen () used stripped eggs of C. gigas for triploid induction by CB, and large differences in survival and triploid ratio were discovered.…”
Section: Discussionmentioning
confidence: 99%
“…50% PB1 release is an obvious sign to begin the induction process in polyploidy production. In triploid induction of Hong Kong oysters by inhibiting PB2 release of diploid or triploid zygotes, the timing of 50% PB1 expulsion is an indicator to start treatment (Gerard et al, ; Qin et al, ). Tetraploid C. gigas were first successfully produced in 1994 by inhibiting PB1 release of eggs from triploids that had been fertilized with sperm from diploids (Guo & Allen, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many research work were put on the inducement of triploid. In the mid of 1980s, triploid oyster was induced and cultured (Gerard, 1994). In the meantime, researchers all over the world began their work on the physiology and biochemistry of the soft body of the triploid oyster.…”
mentioning
confidence: 99%